The Spartan Drama of Plato's Laws - Friedland, Eli (Political theory for today., 2020)
The Spartan Drama of Plato's Laws is the first interpretation of the Laws to give sustained consideration to Megillos, the only character from Sparta that Plato created. Eli Friedland shows the profound importance of character to the Laws, and the rich drama of Plato's longest, and supposedly driest, work.